The Key to Child Independence Starting at Home: A Case Study on The Role of Parenting Styles and Practical Life Skills - Putri, Novenda Cahya Awika; Wiyono, Bambang Budi; Putra, Yudithia Dian (Yayasan Indonesia Emerging Literacy Education, 2025)
This study aims to examine how parental parenting affects the development of practical life skills in early childhood. Using a qualitative approach with a case study design, data was collected through participatory observation and in-depth interviews with parents and educators of children aged 4-6 years. Data analysis is carried out through data reduction, data presentation, and conclusion drawing and verification, accompanied by triangulation techniques to increase the validity of findings. The results showed that authoritative parenting styles were most effective in fostering children's independence, while permissive and authoritarian parenting tended to inhibit such development. Parents' challenges are generally related to time constraints, social pressures, and cultural norms that do not support children's exploration. Socio-cultural and environmental factors have been shown to mediate the effectiveness of parenting significantly. The implications of this study confirm the importance of building a consistent, responsive, and contextual parenting ecosystem in supporting children's life skills. These findings are expected to be an important contribution to the development of early childhood education policies that are more adaptive to social and cultural dynamics of society.